Insight into Bone Metabolism and Skeletal Mass in Polycystic Ovary Syndrome - Zehra Berberoglu (European Medical Journal, 2015)
Polycystic ovary syndrome (PCOS) is a complex, multifaceted disorder that manifests with obesity, hyperandrogenaemia, hyperinsulinaemia, and possibly hyperoestrogenaemia. These clinical features can cause PCOS to positively influence bone mass, and new relationships between obesity, bone remodelling, and energy metabolism have emerged. Bone mass can also be influenced by interrelated metabolic events that are not necessarily mediated by androgens. This article summarises the current literature with respect to the associations between the diverse clinical components of PCOS and bone.